AFFIRMATIVE ACTION ATAU SELECTIVE JUSTICE (Study Pelanggaran Lalu Lintas Yang Dilakukan Oleh Orang Papua Di Kota Yogyakarta) - Rivaldhy N. Muhammad; M Jeffri Arlinandes Chandra; Abdul Mutalib (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: The phenomenon of traffic violations in Indonesia seems to describe a significant increase. Traffic violations, especially in the city of Yogyakarta, seem to give a stereotype that those who often violate traffic rules are Papuans (students). The research approach used is a qualitative approach, a research approach oriented to natural phenomena. Using this type of qualitative descriptive research which is intended to collect information about an existing symptom. Data collection techniques in this study are through observation, interviews and documentation studies. The data will be obtained based on the type and source by analyzing the data qualitatively. Realistically, there are several traffic violations committed by Papuans, especially students who live in the city of Yogyakarta, including not wearing a helmet and riding a ride with more than two people, giving rise to the interpretation that Papuan students are immune to the law or selective justice/affirmative action in terms of traffic violations. .Keywords: Affirmative Action; Selective Justice; Traffic violations